(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As regards environmental security, ecotourism is the most significant factor. In India, the tourism of wildlife is rising fast. It draws many visitors from home and abroad. Wildlife tourism is one of the major sources of revenue, considering the growing number of visitors. If ecotourism expands quickly beyond its boundaries, it can contribute to a variety of political, social and cultural issues. An growing number of visitors above the carrying capacity can deteriorate the areas as lodging, shopping centers and other leisure facilities in wildlife areas are increased. It is threatened by wiping plants and animals and may contribute to the artificial habitat substitution of the natural world.This research would allow sustainable wildlife tourism activities to be understood and adopted. Via financial contributions, non-financial investments, socio-economic benefits and education, sustainable tourism is having a positive impact. This fulfills the Reserve’s intent.